Surgical anatomy of the orbit. A systematic and clear study of a complex structure - Villalonga, Juan F; Sáenz, Amparo; Revuelta Barbero, Juan M; Calandri, Ismael; Campero, Álvaro (Neurocirugia (Asturias, Spain), 2019)
The orbit is a structure of interest for many medical specialties. Surgical approaches to the orbit present significant difficulties for the general neurosurgeon. Whoever decides to practice orbital surgery must have vast anatomical knowledge of this structure. However, although many of the existing publications about orbital anatomy show the complexity of this structure in detail, they fail to facilitate their understanding. The purpose of this study was to systematise and simplify the anatomical study of the orbit from a surgical perspective, to facilitate its understanding. A review of the international literature on the subject was carried out, and the principle of the rule of 7was followed for its ordering. For illustration purposes, photographs of cadaveric preparations and digital drawings were used. The orbits are 2cavities located symmetrically on both sides of the nose. They have a pyramidal shape, with 4sides, a posterior vertex, an anterior base and their axis established from the sagittal plane at a 20-degree angle. A distinctive feature of the orbit is that its elements are organised into groups of seven: 7bones, 7intraorbital extraocular muscles and 7nerves. A systematisation of the orbital anatomy was performed with clear illustrations to simplify its study. The understanding of the anatomy of the orbit is vital to classify lesions and provides a solid basis when choosing the most appropriate approach for their treatment.